PRAKTEK PERATAAN LABA: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Indriana Kurniawati (Fakultas Bisnis UKDW, 2011)
Income smoothing is an action to increase or decrease profit resulted by a firm in order that its profit looks to be stabile or not to be fluctuated. The purpose of this research is to find out the effect of the measurement of firm, profitability, financial leverage, dividend payout ratio, and industrial sector toward the practice of profit instrument in firm registered in Indonesian stock exchange. Observation is done for 5 years, namely from the year 2004 to 2008. Sample used in this research was totaled 173 firms, all of them classified more to the group of firm which did not or make average profit using Eckel Index. The result of this research showed that the measurement of firm, net profit margin, and dividend payout ratio did not influence the practice of income smoothing. While return on equity, financial leverage, and industrial sector were influenced the practice of income smoothing.Keywords: income smoothing, eckel index, profitability.